Motherhood confined - Bennett, Rachel E. (Manchester University Press, 2024)
Should pregnant women be sent to prison? Is prison a place for the birth and care of babies? Can it ever be? This book is the first extensive historical examination of how the modern prison system sought to answer these perennial questions. The book takes the reader through the prison gates to demonstrate that, although a common feature of everyday life in women’s prisons, pregnancy, birth and motherhood were rarely fully considered at policy level. Instead, the experiences of mothers and children were shaped by a myriad of factors including debates about reconciling the management of institutional discipline with the maintenance of health and issues of gender and class. Lamented as an inalienable heritage of woe but also as an opportunity for the closer supervision of mothers, prison births evoked intense debate and required the negotiation of obdurate regimes. The book reveals how oscillating debates about the purpose of prisons shaped the punitive, reformatory and medical treatment of confined mothers. It also challenges scholarly debates about institutional discipline by delving further into the role of prisoners and prison staff in shaping the terms of their incarceration.